2015
DOI: 10.1111/pai.12372
|View full text |Cite
|
Sign up to set email alerts
|

Decline in admissions for childhood asthma, a 26‐year period population‐based study

Abstract: There has been a substantial decline in the rate of hospital admissions for childhood asthma after 1989/1990, with major differences between age groups and genders. The decline could be due to improved care of children with asthma or a real reduction in asthma exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Although the decrease in hospitalizations has included all population groups, the average of decline in children was lower, mainly under the age of 4 years. This finding particularly in younger children were also described in other studies [3,9] and could be explained due to differences on the diagnosis of asthma in children 5 years of age and younger.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although the decrease in hospitalizations has included all population groups, the average of decline in children was lower, mainly under the age of 4 years. This finding particularly in younger children were also described in other studies [3,9] and could be explained due to differences on the diagnosis of asthma in children 5 years of age and younger.…”
Section: Discussionsupporting
confidence: 84%
“…Hence, specific public health strategies to protect vulnerable populations as subjects with asthma should be pursued. Although the global prevalence of asthma has been rising worldwide, some studies have shown that the number of hospitalizations tend to fall in some developed countries [2,3], at least partially explained by improved medical care and wide access to controller therapy, such as inhaled corticosteroids (ICS) [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…21 The decrease in hospitalization rate could reflect global decreases in the frequency and severity of asthma exacerbations seen in the western world. 8,22,23 Non-physiological factors, such as changes in asthma education, evidence-based therapy (change of treatment protocol), access to ambulatory healthcare, and criteria for hospitalizations, may have contributed as well. 24,25 Tobacco smoke exposure may play a part as well with clear evidence of its role in asthma admissions.…”
Section: Discussionmentioning
confidence: 99%
“…A study from France showed that the decline in admissions was only seen for adults, with stable rates for children 6 as reported in a study of Danish children 7 . In contrast, the number of children hospitalized for asthma in Norway showed a continuous decline up to 2010 8 . Stable or declining rates of admissions, despite increased prevalence, have been attributed to a combination of factors, primarily, better comprehension of the mechanisms leading to exacerbations, better outpatient care and proactive care with regular controller therapy 9,10 …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation